Hydrothermal synthesis of Group 13 metal trifluoride complexes with neutral N-donor ligands12. Issue 20 (28th May 2015) - Bhalla, Rajiv; Levason, William; Luthra, Sajinder K.; McRobbie, Graeme; Monzittu, Francesco M.; Palmer, Jazmyn; Reid, Gillian; Sanderson, George; Zhang, Wenjian
<x xml:space="preserve">Abstract</x> MF3·3H2O (M = Al, Ga or In) react with neutral imine ligands under hydrothermal conditions to yield mer-trifluoro complexes with extensive H-bonding.